Systolic hypertension and duration of diabetes mellitus are important determinants of retinopathy and microalbuminuria in young diabetics - Nazaimoon, E.M.W.; Letchuman, R.; Noraini, N.; Ropilah, A.R.; Zainal, M.; Ismail, I.S.; Mohamad, W.B.; Faridah, I.; Singaraveloo, M.; Sheriff, I.H.; Khalid, B.A.K. (1999)
This cross-sectional study looked at the prevalence of microalbuminuria and retinopathy in a cohort of 926 young, Type 1 and Type 2 diabetes mellitus (DM) patients, and determined the factors which were associated with these microvascular complications. The prevalence of microalbuminuria, defined as the albumin:creatinine ratio greater than or equal to 2.5 (for males) or greater than or equal to 3.5 mg/mmol (for females), was 13.4 in Type 1 DM, 69.5 in insulin-requiring Type 2 DM and 16 in Type 2 DM treated only with oral hypoglycemic agents. Compared to those with normal renal functions, these patients were older (P less than or equal to 0.01), had significantly elevated blood pressures (P < 0.01 or P = 0.0001), and in the case of Type 1 DM, with a higher body mass index (P = 0.0001) and waist-hip ratio (P < 0.01). The prevalence of diabetic retinopathy in Type 1 DM was found to increase with the duration of diabetes, from 1.4 in the newly-onset (< 5 years), to 9.9 in those with 5-10 years disease, to 35 among patients with more than 10 years of diabetes (P < 0.0001). In this study, it was also observed that 10 of the Type 1 DM patients already had retinopathy within 5 years of diagnosis, and the prevalence increased significantly to 42.9 (P < 0.0001) among patients who had been diabetics for more than 10 years. Stepwise multiple regression analysis showed that besides the disease duration, systolic blood pressure was the most common and significant determinant for both microalbuminuria and retinopathy in both types of DM, thus implying that in order to reduce the risk of microvascular complications in diabetes mellitus, systolic and not just the diastolic blood pressure, should be effectively controlled. (C) 1999 Elsevier Science Iceland Ltd. All rights reserved.